CuCo2O4‐Gd0.1Ce0.9O1.95 as a Potential Cathode Material for Intermediate Temperature Solid Oxide Fuel Cells. Issue 2 (20th December 2016) - Shao, Lin; Wang, Pengxiang; Sun, Chengzhi; Fan, Lishuang; Zhang, Naiqing; Sun, Kening
Abstract: CuCo2 O4 ‐Gd0.1 Ce0.9 O1.95 (GDC) composite was investigated as a potentially promising cathode material for intermediate temperature solid oxide fuel cells (IT‐SOFCs). The CuCo2 O4 ‐GDC composite cathodes were characterized via X‐ray diffraction, scanning electron microscopy and thermal expansion. CuCo2 O4 ‐GDC composites exhibited a good chemical compatibility and thermal compatibility for each composition. Introduction of the GDC nanoparticles increased the length of TPBs and enhanced the electrochemical activities of the CuCo2 O4 ‐GDC composite cathode. The polarization resistance with addition of 60 wt.% of GDC showed the least value of 0.09 Ω cm 2 at 800 °C. The results demonstrated that CuCo2 O4 ‐GDC composite would be a promising cathode material for IT‐SOFCs. Abstract : CuCo2 O4 ‐Gd0.1 Ce0.9 O1.95 composite is investigated as a promising cathode material for IT‐SOFCs. The CuCo2 O4 ‐GDC composite cathodes exhibit low polarization resistance (0.09 Ω cm 2 at 800 °C) and high power density (1074 mW cm −2 at 800 °C).